Competency-based Human Management Model at the CIAUTO vehicle painting department in Ambato, Ecuador - Mena Reinoso, Angel Patricio (2020)
This study was conducted at the Ciudad del Auto (CIAUTO) company in Ambato, Ecuador, owned by motor vehicle company Great Wall. First, a literature review was conducted where jobs were identified in order to design roles using the Delphi method; the activities performed by each worker in their role were also described. In addition, the process of competency-based human talent management in the painting department was developed using the processes of admission, application, compensation, development, maintenance, personnel monitoring and strengthening the human talent department. Subsequently, a pre-experiment performance measurement based on management indicators was conducted using the Likert Scale to assess the degree of employee satisfaction, focused on attitudes, which resulted in an increase in job satisfaction from 31.25% to 46.25%. Finally, upon validation of the hypothesis using the Chi-square test, it can be said that the competency-based human management in the CIAUTO painting department improves its processes and procedures and increases productivity.